Fluoride in dental practice - Dorota Ochyra; Bartłomiej Ochyra (Kazimierz Wielki University, 2018)
Fluoride occurs naturally in our environment and we are exposed to it every day. In the right doses, it is very effective and helpful. Fluorine has many valuable functions, besides as enamel strengthening, it has bacteriostatic effect. However, in comparison to positive effects, fluoride can be toxic to the patients. The effect of fluoride on retention and prevention of caries is very significant, which has been proved in scientific studies.